Detailed understanding on thermodynamic and kinetic features of phenanthrene hydroprocessing on Ni‐Mo/HY catalyst. Issue 11 (2nd August 2022) - Peng, Chong; Liu, Peng; Zhou, Zhiming; Fang, Xiangchen; Pan, Yun‐Xiang
Abstract: Phenanthrene hydrogenation is a key reaction for improving the quality of gasoline and diesel. Herein, we conduct detailed thermodynamic and kinetic analyses for phenanthrene hydrogenation on a Ni‐Mo/HY catalyst. We establish a comprehensive reaction network for phenanthrene hydrogenation, and calculate equilibrium constant, rate constant, adsorption constant, activation energy barrier, and reaction energy for each step in the reaction network. All of the steps in the reaction network are revealed to be exothermic. A kinetic model with 28 parameters is constructed for phenanthrene hydrogenation. The deviation of the product yields calculated by the kinetic model from those obtained in experiments is less than 4.5%, indicating the reasonability and accuracy of the kinetic model. The most favorable pathway for phenanthrene hydrogenation is demonstrated to be phenanthrene → tetrahydrophenanthrene → sym‐octahydrophenanthrene → 5, 6‐butyl‐tetrahydronaphthalene → tetralin. These results are helpful for efficiently tuning catalyst properties and optimizing reaction conditions for enhancing phenanthrene hydrogenation.